Penelitian proses pengapuran â pembuangan bulu menurut methoda Herfeld - Oetojo, Bambang; Luthfie, Muchtar; Widari, Widari; Widhiati, Widhiati; Basalamah, Hasan (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1995)
The possibility to apply unhairing liming method of Herfeld in Indonesia is the purpose of this research. As a comparison it was perform unhairing and liming method of the institute for Research and Development of Leather and Allied Industries (IRDAI). In this research used 18 piecies of green salted cured goat skin. For each treatment used 3 pieces of green salted cured goat skin and it was done three times. The pelts output were visually investigation for the loose of the hair, the condition of the grain surface and the plump. The output of the visually investigation point out, that the hair were loose easily, the condition of the grain surface of the pelts were clean and the pelts were well plump. Practical meaning of this research is, unhairing and liming method of herfeld may be applied in Indonesia.Â INTISARIÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Kemungkinan untuk menerapkan proses pengapuran dan pembuangan bulu menurut metode Herfeld di Indonesia adalah tujuan dari penelitian ini. Sebagai pembanding dikerjakan pula proses pengapuran dan pembuangan bulu menurut metoda Balai Besar Penelitian dan Pengembangan Industri Barang Kulit, Karet dan Plastik (BBKKP). Dalam penelitian ini menggunakan 18 lembar kulit kambing yang diawet dengan garam, untuk setiap perlakukan menggunakan 3 lembar kulit kambing yang diawetkan dengan garam dikerjakan 3 kali. Kulit pelts yang dihasilkan diamati secara visual mengenai lepasnya bulu, keaadan raja kulit dan kebengkakan kulit bersih dan kebengkakan kulit baik. Arti praktis dari penelitian ini adalah, proses penggapuran dan pembuangan bulu menurut metoda Herfeld dapat diterapkan di Indonesia.